Institutions and the Path to the Modern Economy: Lessons from Medieval Trade (an Excerpt) - Greif, Avner (Journal of Economic Sociology, 2012)
Varieties in economics, politics and societies are widely considered to be resulted from the influence of different institutions. However, economists, political scientists, and sociologists do not come to agree about what institutions are, which forces contribute to the maintenance of institutions and their changes, and how it is possible to affect institutions development. The author proposes an understanding of institutions which integrates outwardly opposite perspectives of institutional approach in social sciences. His conception gives opportunities to deal with institutional roots, maintenance, endogenous changes and the influence of previous institutions on the successive ones. The journal «Economic Sociology» publishes the second chapter «Institutions and Ttransactions» in which the author defines the key concepts of his study in institutional backgrounds for markets and states.